KEANEKARAGAMAN SERANGGA MUSUH ALAMI PADA PERTANAMAN BAWANG MERAH (Allium ascalonicum L) YANG DIAPLIKASI DENGAN BIOINSEKTISIDA Beauveria bassiana (Bals.-Criv.) Vuill. - Riski Kaleb; Flora Pasaru; Nur Khasanah (Universitas Tadulako, 2015)
The purposeof this study was to determine the diversity of natural enemy insect in the ecosystems ofshallotcrops applied withbio-insecticide Beauveria bassiana. The research was conducted in two different fields name lyapplied with and without bio-insecticide Beauveria bassiana located in Bolupontu Village, Sigi District of Central Sulawesi Province, from Mayto August 2014. Sampling was collected using two method sinsectnets (Sweep Net) and insecttrap of(Pitfall Trap). Dataanalysis used the Shannon-Wiener indexand T-Test.The results showed thatthe diversity ofnatural enemy insect sonshallot crop applied with bio-insecticide Beauveria bassiana was higherthan on that withoutbio-insecticide. Keywords : Bioinsecticide Beauveria Bassiana, Diversity, Insect Natural Enemies, Shallot.